Using normalisation process theory to identify factors facilitating the scaling up of parenting programs for immigrant parents - Osman, Fatumo; Schön, Ulla-Karin; Salari, Raziye (Frontiers in Psychology, 2024)
Objective: As most studies focus on the initial adaptation of culturally tailored parenting programs in real-world settings, scalability and sustainability remain understudied. In this study, we used normalization process theory (NPT) as a conceptual framework to identify and understand the contextual factors impacting the scalability and sustainability of a culturally tailored parenting program, Ladnaan, in three Swedish municipalities.Method: Nineteen managers, coordinators, and group leaders completed a survey and participated in individual or focus group interviews.Results: Our analyses showed that participants agreed on the need for the Ladnaan intervention among immigrant families. However, they were concerned that insufficient resources may hinder the recruitment and retention of parents, particularly as certain resources were allocated to the delivery of other, non-evidence-based interventions. Both managers and coordinators emphasized that embedding Ladnaan into everyday practice is conditioned on the collective work and engagement of all stakeholders, which will occur only if local authorities feel they own the program. The recruitment and retention of group leaders was mentioned as a key challenge in sustaining Ladnaan as the need for the program fluctuated over time.These findings highlight the importance of promoting evidence-based programs within the services available for forcibly displaced parents, and of coordinating efforts to scale up and sustain these programs.